Perimbangan Keuangan Pemerintah Pusat-Daerah dalam Pelaksanaan Otonomi Daerah di Provinsi Bali - Komang Pradnyana Sudibya (Universitas Pendidikan Nasional, 2020)
The Law No. 23 of 2014 on Regional Government and the distribution of regional taxes and levies by the Law No. 28 of 2009 on Regional Taxes and Regional Levies which are the right of regency/city government, the implication is that there is a big gap in the area of local revenue (PAD) which affects the imbalance of development between regions and equitable distribution of public welfare. To overcome this income inequality, the central government has an instrument through a central-regional financial balance to overcome both vertical and horizontal gaps. From the revenue structure, it turns out that the income of the financial balance of the central-regional is far greater than the local revenue. This indicates that the regional government still depends on the central government and the balance fund formula is an expectation for the regencies/city in Bali. This research uses normative legal research. The result of the research shows that the source of local revenue for regencies / cities throughout Bali, it turns out that the funds originating from the central financial balance in the regions are greater than the original regional income. This is a parameter that the regions still have a high dependence on the central government in obtaining financing for the implementation of regional autonomy. Keywords: Income inequality, local revenue and financial balance